TRAINING FOR TEACHING FRENCH AS A FOREIGN LANGUAGUE IN AGERIA, WHAT CHALENGES? - Ali BOUZEKRI (Universitaria Publishing House, Craiova, 2024)
The article examines the differences in the pre/professionalizing components of training programs between two university institutions (Sorbonne vs. Alger2), and evaluates how these programs influence the development of professional identity among French language graduates in Algeria. The results of our study are based on a survey of education professionals, as well as a comparison between two training offerings aimed at identifying shortcomings in training offerings in Algeria, which enables providing recommendations to strengthen the professionalization of French language undergraduate students in Algeria.